Optimal delivery time for patients with diet-controlled gestational diabetes mellitus: a single-center real-world study - Zongzhi Yin; Tengteng Li; Lu Zhou; Jiajia Fei; Jingjing Su; Dan Li (BMC, 2022)
Abstract Background To determine the optimal delivery time for women with diet-controlled gestational diabetes mellitus by comparing differences in adverse maternal-fetal outcome and cesarean section rates. Methods This real-world retrospective study included 1,050 patients with diet-controlled gestational diabetes mellitus who delivered at 35-42 weeks' gestation. Data on patient characteristics, maternal-fetal outcomes, and cesarean section rate based on fetal gestational age were collected and analyzed. Differences between deliveries with and without iatrogenic intervention were also analyzed. Results The cesarean section rate at ≥ 41 weeks' gestation was significantly higher than that at 39-39 + 6 weeks (56% vs. 39%, p = 0.031). There were no significant differences in multiple adverse maternal or neonatal outcomes at delivery before and after 39 weeks. Vaginal delivery rates were increased significantly at 39-39 + 6 weeks due to iatrogenic intervention (p = 0.005) and 40-40 + 6 weeks (p = 0.003) in patients without and with spontaneous uterine contractions, respectively. Conclusions It's recommended that optimal delivery time for patients with diet-controlled gestational diabetes mellitus should be between 39- and 40 + 6 weeks' gestation. Patients who have Bishop scores higher than 4 can undergo iatrogenic intervention at 39-39 + 6 weeks. However iatrogenic interventions are not recommended for patients with low Bishop scores.